Masking Unmasked - Simon, E. author. aut Link
XX, 185 p.
Keywords: Acting with masks is one of the most ancient stage techniques still in use today. Masking Unmasked is a basic guide to using this ancient art to develop character and movement in four sections that correspond to mask size: Full-Face Masks, Clowning, Bag Masks, and Half-Face Masks. Each section addresses fundamental acting principles and shows how the ancient technique can be applied to the contemporary stage. It is the perfect book to use as background to traditional, non-masked acting principles. For instance, mask acting provides a great way of strengthening core acting skills. Actors in masks experience the primary goal of acting because they are required to tap into profound physical, vocal, emotional, and psychological transformations in the course of creating a character. In addition, masking promotes honest, believable, and detailed work. Illustrated profusely throughout, the hands-on exercises developed by Simon teach actors to shift cleanly between beats, execute moment-to-moment specificity, unleash creative impulses, take risks and expand character range, power and vulnerability. Masking Unmasked is a book of ancient acting techniques that are indispensable for the actor of today.